OUTCOMES OF RHEGMATOGENOUS RETINAL DETACHMENT REPAIR AFTER FAILED PNEUMATIC RETINOPEXY. Issue 5 (May 2020) - Vidne-Hay, Orit; Abumanhal, Muhammad; Elkader, Amir Abd; Fogel, Miri; Moisseiev, Joseph; Moisseiev, Elad
Abstract : Purpose: To evaluate the visual and anatomical outcomes of reoperations following failure of pneumatic retinopexy (PR) for rhegmatogenous retinal detachment repair and compare the different surgical techniques used in these cases. Methods: The study included 114 eyes of 114 patients who underwent PR for rhegmatogenous retinal detachment and required subsequent surgery for its repair. These included repeated PR, scleral buckling, vitrectomy with gas or silicone oil, and vitrectomy with scleral buckling. The groups were compared for rates of retinal reattachment, visual improvement, and the occurrence of recurrent rhegmatogenous retinal detachment and any other postoperative complications. Results: In 91 (79.8%) eyes, the retina was reattached with one additional procedure. The success rate was significantly lower in eyes treated by repeated PR than by other surgical techniques (33 vs. 76–90%; P < 0.001). Visual acuity after PR failure was not significantly different than that at presentation and had improved significantly after surgery for retinal reattachment ( P < 0.001). Conclusion: Pneumatic retinopexy failure was not associated with visual acuity loss, and the outcomes in 79.2% of cases that required only one additional surgery are comparable with those achieved with primary surgery. Poor outcomes were associated with eyes that required more than one additional surgery and that suffered complications. Abstract : This is the largest series of pneumatic retinopexy failures. Outcomes were favorable with all subsequent surgical procedures except for repeated pneumatic retinopexy, which had a significantly lower success rate. Reattachment was achieved with only one additional surgery in 79.2% of cases, with visual outcomes comparable with those of primary surgery.